Ultrasound measurement of vastus lateralis and vastus medialis muscle parameters to identify chronic thyrotoxic myopathy - Shi-en Fu; Rou-mei Wang; Xing-huan Liang; Jing Xian; Jie Pan; Xue-lan Chen; Cheng-cheng Qiu; Zhi-ping Tang; Ying-fen Qin; Hai-yan Yang; Li-li Huang; Ya-qi Kuang; et al. (Endocrine Connections, 2023)
Introduction: Chronic thyrotoxic myopathy (CTM) is a common, easily neglected complication of hyperthyroidism. There are currently no standard diagnostic criteria for CTM, and the ultrasonic characteristics of CTM-affected skeletal muscle remain unclear. Herein, we aimed to evaluate hyperthyroid patients for CTM by ultrasound and identify ultrasonic muscle parameter cutoffs for CTM diagnosis. Materials and methods: Each participant underwent ultrasonography. The original (muscle thickness (MT), pennation angle (PA), and cross-sectional area (CSA)) and corrected (MT/height (HT), MT/body mass index (BMI), CSA/HT, and CSA/BMI) parameters of the vastus lateralis and vastus medialis (VM) were evaluated. The diagnostic effectiveness of ultrasound for predicting CTM was determined using receiver operating characteristic (ROC) curve analysis. Our study included 203 participants: 67 CTM patients (18 males, 49 females), 67 non-CTM patients (28 males, 39 females) and 69 healthy controls (20 males, 49 females). Results: The CTM group had lower muscular ultrasonic and anthropometric parameters, higher thyroid hormone and thyroid-stimulating hormone receptor antibody (TRAb) levels, and a longer duration of hyperthyroidism than the non-CTM group (P < 0.05). The VM-PA, VM-CSA, VM-CSA/HT, and VM-CSA/BMI were lower in females than in males (P < 0.05). Free thyroxine (FT4) and TRAb both showed significant negative correlations with VM-MT, VM-MT/HT, VM-CSA, and VM-CSA/HT (P < 0.05). VM-MT/BMI and VM-CSA/HT, respectively, best predicted male and female CTM (AUC = 0.84, 0.85; cutoff ≤ 0.07, < 4.01). Conclusion: Ultrasound measurement of muscular parameters, especially in the VM, is a valid and feasible way of diagnosing and characterizing possible CTM in hyperthyroidism.